Post-Traumatic Validative Incidentals Amongst Tertiary Students - Christiani, Ribka Wahyu; Yappo, Yohanes; Rudie (CV. Edujavare, 2023)
Traffic accidents as painful experiences can lead to various forms of psychological harm, such as mental illness, trauma, post-traumatic stress disorder, and depressive symptoms. However, human responses to pain-related events may vary. This study aimed to understand how accident survivors learn to make sense of their accident and how it impacts their daily lives. According to the research findings, some subjects still have difficulty accepting themselves after experiencing psychological distress and emotional shock. In contrast, others are motivated due to various situations and events that impact their psyche and daily life. The findings of this study also show that teaching a skill to subjects can improve their quality of life compared to not teaching it to them.